Health promotion media design: food traffic light video to prevent type 2 diabetes mellitus in elementary school children - Tutstsintaiyn, Ribia; Supriyati; Huriyati, Emy (BKM Public Health and Community Medicine, 2021)
Purpose: Annually, 15% to 45% of newly diagnosed type 2 diabetes mellitus (DM) cases in children are observed. Among the contributing factors is an unhealthy diet, characterized by high sugar, fat, and carbohydrate intake, as well as low fiber consumption. This study aims to design an animated video of food traffic lights (FTL) for elementary school students to prevent DM. Methods: Qualitative research with a participatory action research approach. The informants were selected based on a purposive sampling technique. The inclusion criteria are fifth-grade students at Gondolayu Elementary School who are willing to participate as research subjects and possess good communication skills. Key informants included classroom teachers, physical education teachers, parents, and experts in media, nutrition, and health promotion. Data were collected through focus group discussions and in-depth interviews, and analyzed using OpenCode 4.03. Results: The students’ problems include risk factors such as frequent consumption of sweet foods, a family history of DM, and a lack of information about DM at school. The design of the FTL video was developed based on a preliminary analysis of students’ needs and interests. The video contains two main components: educational content on DM and the FTL concept. Conclusion: The animated food traffic lights video can elicit a positive response from students, parents, and teachers at school. The design of an FTL animation video must consider the needs, target character, and detailed components within the video.